'It depends what you mean by the term rights': strata termination and housing rights. Issue 1 (2nd January 2017) - Troy, Laurence; Easthope, Hazel; Randolph, Bill; Pinnegar, Simon
Abstract: Strata title was introduced in Australia over 50 years ago and offered a legal mechanism for space to be vertically subdivided and traded. Importantly, it allowed individualised property rights to be applied to multi-unit housing. In New South Wales, recent changes to the Strata Scheme Development Act allow termination of strata schemes with less than unanimous support of owners. A central feature of the discussion surrounding the implementation of these changes was to question the rights associated with ownership of strata. This paper presents findings from key-informant interviews undertaken in the lead up to the reforms to the NSW legislation governing strata termination. Analysis of these interviews demonstrates the complex ways in which property rights are understood in relation to strata termination within the broader context of housing. This paper argues that successful implementation of the new legislation impacting upon property rights in strata will require concerted engagement with wider social concepts and understanding of housing within the Australian community.